Approximation algorithms for the integrated path and bin packing problem - Li, Weidong; Sun, Ruiqing (R.A.I.R.O. Recherche opérationnelle, 2025)
In this paper, we consider the integrated path and bin packing problem, which to use the minimum number of unit-size bins to packing the arcs on the path between two specific vertices in a given directed graph. We propose a 3/2-approximation algorithm and an asymptotic polynomial time approximation scheme.